Kebijakan Merdeka Belajar dan Implikasinya terhadap Pengembangan Desain Evaluasi Pembelajaran Pendidikan Agama Islam - Syamsul Arifin; Nurul Abidin; Fauzan Al Anshori (Universitas Pesantren Tinggi Darul 'Ulum, 2021)
This article was written to examine the policy form of the Republic of Indonesia’s Minister of Education and Culture and its development toward the evaluation of Islamic religious education (PAI) learning. This article was written using a qualitative research method with a literature study approach. Data for the literature study were gathered through a process of scrutiny, analysis, and presentation of findings. According to the results of the literature review, the Ministry of Education and Culture’s, Nadiem Makarim, policy is known as the “Freedom of Learning” policy. This policy addresses four issues: national standard school exams (USBN) developed by each school; changes to the national exam (UN) to a minimum competency assessment and character survey; educators’ freedom to design lesson plans (RPP); and flexibility in new student admissions regulations (PPSB). “Merdeka Belajar” is distinguished by its creativity, learning orientation toward problem solving, needs-based learning, and integration into the workplace, as well as a comprehensive assessment system. This has an impact on the need for PAI learning evaluation development. This article concludes that evaluation evaluation is based on the purpose of human birth as ‘abdun and caliph; PAI learning evaluation includes aspects of ‘aqliya, bāṭiniya, and ‘amaliya; and PAI learning evaluation is carried out to balance the power of thought, dhikr, and charity.